The Role of Independent Commissioners, Audit Committee, Audit Committee Expertise, Activities of the Audit Committee and Leverage on Earnings Management - Sunarso, Ulfi Amalia; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of independent commissioners, the size of the audit committee, the expertise of the audit committee, the activities of the audit committee and leverage on earnings management in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. This study uses a purposive sampling technique with 160 annual reports and financial statements with 40 infrastructure companies. The analysis used in this study uses multiple linear regression analysis using SPSS version 26 as the calculation tool. Based on the results in this study, it is shown that independent commissioners, audit committee size and leverage have no effect on earnings management. Meanwhile, the expertise of the audit committee and the activities of the audit committee have a positive effect on earnings management. The predictive ability of the five variables on earnings management was 69.3% while the other 30.7% came from other variables.